Cleanliness culture as hidden curriculum: An empirical study of character internalisation in primary education - Taufikin Taufikin (Indonesian Journal of Learning and Educational Studies, 2024)
This study examines the pre-learning cleanliness culture as a mechanism of the hidden curriculum in the internalisation of character among elementary school students. Using a qualitative case study approach, data were collected through observations, in-depth interviews and documentation of school practices. The findings reveal that the internalisation of values does not occur through formal instruction but rather through repeated practices that directly shape moral experiences. Three main dimensions were identified: behavioral habituation that establishes patterns of discipline, teacher modeling that provides moral legitimacy, and school structures that maintain the consistency of these practices. The interaction of these three elements forms an implicit learning ecosystem in which values manifest as lived actions rather than merely as taught concepts. These findings also reveal that, without reflection, practices can lead to mechanical compliance, requiring a balance between action and awareness. The novelty of this research lies in the conceptualisation of the Embodied Hidden Curriculum, which positions everyday practices as the primary locus of character formation. This research contributes to expanding the discourse on character education by emphasising that the power of moral transformation often lies in simple actions consistently repeated within school life.